Measuring evolutionary rates of proteins in a structural context [version 2; referees: 4 approved] - Dariya K. Sydykova; Benjamin R. Jack; Stephanie J. Spielman; Claus O. Wilke (F1000Research, 2018)
We describe how to measure site-specific rates of evolution in protein-coding genes and how to correlate these rates with structural features of the expressed protein, such as relative solvent accessibility, secondary structure, or weighted contact number. We present two alternative approaches to rate calculations: One based on relative amino-acid rates, and the other based on site-specific codon rates measured as dN/dS. We additionally provide a code repository containing scripts to facilitate the specific analysis protocols we recommend.